Method Development for Pesticide Determination in Paddy Rice Using Near Infrared Spectroscopy - Rungchang, S.; Numthuam, S.; Charoensook, R.; Thongkum, P.; Junmatong, C. (International Journal of Agricultural Technology, 2018)
A growing world population leads to an increase in demand for agricultural products and food. In order to increase crop yield, pesticides have been extremely used, resulting in a high risk to environment and human health. A large number of pesticides are used on paddy rice field in Southeast Asia countries. Carbofuran is a highly toxic insecticide to vertebrates that has been illegally used on paddy field and other crops in developing country with a poor application and management. In order to maintain public health condition, the control and determination of pesticide residues in agricultural products is extremely needed. This study aimed to investigate the feasibility of near infrared (NIR) spectroscopy for a rapid determination of carbofuran in paddy rice. Thai jasmine paddy rice artificially contaminated with carbofuran ranging from 0-50 ppm was used as samples. The NIR measurements of the paddy rice were performed using reflectance FT-NIR spectroscopy as a nondestructive determination. The attempt to improve prediction efficiency of carbofuran residue was then performed using the dry-extract system for (near) infrared (DESIR) technique. The reflectance NIR spectra of DESIR samples were also obtained. For data analysis, partial least square (PLS) regression was used to develop a calibration model for the carbofuran prediction. It was found that the spectra of the contaminated paddy rice provided insufficiently accurate calibration results with coefficient of determination (R2) of 0.87 and root mean square error of prediction (RMSEP) of 7.20 ppm. Superior prediction accuracy was obtained from the calibration model based on the spectra of DESIR samples (R2 = 0.99, RMSEP = 3.05 ppm). It was concluded that NIR spectroscopy combined with DESIR technique had a potential to be a rapid and effective method for the determination of carbofuran in paddy rice. This method could become a powerful tool for coping with the environmental and health risk caused by a misuse or overuse of pesticides.